Pengaruh Likuiditas, Efisiensi Penggunaan Modal Kerja dan Leverage terhadap Profitabilitas pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang terdaftar di Bursa Efek Indonesia - Alamsyah, Agus Rahman; Muchlas, Zainul (LP2M Institut Teknologi dan Bisnis Asia Malang, 2016)
This study aims to determine how much influence the liquidity proxied current ratio (CR), the efficiency of working capital is proxied working capital turnover (WCT) and the leverage that proxy debt to equity ratio (DER) to profitability that proxy return on investment (ROI) on companies Manufacturing Sector Consumer Goods Industry listed in the Indonesia Stock Exchange. The results showed that the variable current ratio (CR) partially no effect on the return on investment (ROI), variable working capital turnover (WCT) partially significant effect on return on investment (ROI) variable debt to equity ratio (DER) is partial no significant effect on return on investment (ROI). Variable current ratio (CR), working capital turnover (WCT), debt to equity ratio (DER) simultaneously affect the return on investment (ROI) at manufacturing consumer goods industry sectors listed on the Jakarta Stock Exchange